From Hungarian Major to Central American Entrepreneur? The Life of Louis Schlesinger in Exile - Szente-Varga, Mónika (FOCUS: Papers in English Literary and Cultural Studies, 2023)
Louis Schlesinger was the son of Henrik Schlesinger and Sarolta Neumann (Erzberg), born in Nagykanizsa, Zala county, on 9 March 1825 (“Latin American Studies”). He joined the cause of the Hungarian War of Independence and was among the defenders of the fortress of Komárom, led by György Klapka. After they surrendered, Schlesinger emigrated overseas, traveling from Liverpool to New York in December 1849. In the US, he met the Venezuelan General, Narciso López (1797-1851), and joined his expedition, aimed at the liberation of Cuba from Spanish rule. The essay discusses the career of Schlesinger as a rubber entrepreneur in El Salvador and as a railroad constructor in Guatemala.